Nitric Oxide Inhibits Hetero-adhesion of Cancer Cells to Endothelial Cells: Restraining Circulating Tumor Cells from Initiating Metastatic Cascade - Lu, Yusheng; Yu, Ting; Liang, Haiyan; Wang, Jichuang; Xie, Jingjing; Shao, Jingwei; Gao, Yu; Yu, Suhong; Chen, Shuming; Wang, Lie; Jia, Lee (Scientific reports, 2014)
Adhesion of circulating tumor cells (CTCs) to vascular endothelial bed becomes a crucial starting point in metastatic cascade. We hypothesized that nitric oxide (NO) may prevent cancer metastasis from happening by its direct vasodilation and inhibition of cell adhesion molecules (CAMs). Here we show that S-nitrosocaptopril (CAP-NO, a typical NO donor) produced direct vasorelaxation that can be antagonized by typical NO scavenger hemoglobin and guanylate cyclase inhibitor. Cytokines significantly stimulated production of typical CAMs by the highly-purified human umbilical vein endothelial cells (HUVECs). CAP-NO inhibited expression of the stimulated CAMs (particularly VCAM-1) and the resultant hetero-adhesion of human colorectal cancer cells HT-29 to the HUVECs in a concentration-dependent manner. The same concentration of CAP-NO, however, did not significantly affect cell viability, cell cycle and mitochondrial membrane potential of HT-29, thus excluding the possibility that inhibition of the hetero-adhesion was caused by cytotoxicity by CAP-NO on HT-29. Hemoglobin reversed the inhibition of CAP-NO on both the hetero-adhesion between HT-29 and HUVECs and VCAM-1 expression. These data demonstrate that CAP-NO, by directly releasing NO, produces vasorelaxation and interferes with hetero-adhesion of cancer cells to vascular endothelium via down-regulating expression of CAMs. The study highlights the importance of NO in cancer metastatic prevention.